Mechanical properties of needle-punched nonwovens for geotechnical applications - Fangueiro, Raúl (2011)
The use of nonwoven fabrics in civil engineering applications has increased significantly in the last years due to the important characteristics and properties of such type of fibrous structure. The functions provided by nonwovens in geotechnical applications include drainage, filtration, separation, soil protection, particularly in its stability and erosion control. In this study the influence of the aerial mass in the nonwovens mechanical properties including tensile, puncture and dynamic perforation (cone drop), have been studied. The results obtained show that there is a significant correlation between the mechanical properties of the geotextiles and the aerial mass. Moreover, the use of a woven fabric as second layer in hybrid structures presents a positive effect to decrease the initial deformation under tensile.